Exposure to Community Violence as a New Adverse Childhood Experience Category: Promising Results and Future Considerations. Issue 1 (January 2017) - Lee, Eunju; Larkin, Heather; Esaki, Nina
Research links high youth exposure to community violence (ECV) with negative health consequences, and the World Health Organization recommends ECV as a new adverse childhood experience (ACE) category. The current study is among the first to include ECV within the ACE categories, examining ACEs and behavioral health (BH) service usage, using a population-based adult sample. Results reveal ECV and ACE associations in the expected direction. Respondents reporting ECV before age 18 had higher ACE scores than those without ECV. Results demonstrate ECV's predictive power for later BH needs and confirm its utility as a new ACE category. Practice implications include attention to ECV among adult populations and mitigating long-term costs through early intervention and prevention.